Animal models of oral infectious diseases - Jing Li; Jing Li; Ya-Nan Zhao; Ya-Nan Zhao; Yi-Hui Wang; Yi-Hui Wang; Yao Chen; Yao Chen; Jia-Long Hou; Jia-Long Hou; Da-Yuan Wang; Linqi Shi; et al. (Frontiers in Oral Health)
Oral infectious diseases, including caries, pulpitis, periodontitis, and oral candidiasis, are caused by plaque biofilm or dysbiosis. These conditions affect over two billion people worldwide, imposing a significant burden on healthcare systems and economies. Developing suitable animal models is crucial for investigating the underlying mechanisms of these diseases and evaluating potential therapeutic strategies. Currently, most animal models of oral infectious diseases are built via inoculating a single pathogenic bacterium. However, these models often fail to fully replicate the complex disease processes observed in humans. As a result, alternative methods are needed to explore more accurate animal models that better represent the progression of oral infectious diseases. Herein, this mini-review provides a concise overview of strategies for constructing animal models of oral infectious diseases, focusing on four representative conditions: caries, pulpitis, periodontitis, and oral candidiasis. The goal is to offer valuable insights and references for researchers working in the field of animal model development for oral health.